2017
DOI: 10.1007/s40620-017-0457-z
|View full text |Cite
|
Sign up to set email alerts
|

Value of the Oxford classification of IgA nephropathy in children with Henoch–Schönlein purpura nephritis

Abstract: Our findings suggest that the Oxford classification is valid for children with HSPN. S and T lesions, which are ignored in the ISKDC classification, can be used to assess renal outcomes of HSPN, and such assessments are not affected by currently available treatments. The value of M, E and C lesions in predicting response to therapy and renal outcome warrants further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 31 publications
4
47
1
Order By: Relevance
“…T1 and 2 lesions were, however, negatively associated with the risk of proteinuria remission while other lesions showed no significant association. Interestingly, the number of biopsies with especially E1 and T1 and 2 in the study by Xu et al [23] differs from ours. This may reflect inter-observer variation between pathologists or differences in patient material and biopsy timing.…”
Section: Discussioncontrasting
confidence: 94%
“…T1 and 2 lesions were, however, negatively associated with the risk of proteinuria remission while other lesions showed no significant association. Interestingly, the number of biopsies with especially E1 and T1 and 2 in the study by Xu et al [23] differs from ours. This may reflect inter-observer variation between pathologists or differences in patient material and biopsy timing.…”
Section: Discussioncontrasting
confidence: 94%
“…The study showed, mesangial proliferation (M1) was significantly associated with tubular atrophy/interstitial fibrosis (T score) and proteinuria. Moreover, crescents in more than 25% of glomeruli (C2) were associated with reduced eGFR (estimated glomerular filtration rate) at the time of biopsy (37). This study showed that patients with endocapillary proliferation (E1), mesangial proliferation (M1), segmental glomerulosclerosis (S1) and extracapillary proliferation (C1 and C2) were more likely to respond to high-dose methylprednisolone.…”
Section: Discussionmentioning
confidence: 68%
“…Another study found that E1 lesions were the only significant variable related to renal outcomes [16]. A study of 104 children showed that S1 lesions were predictors of renal outcome, and T1/T2 were risk factors for nonremission from proteinuria [18]. A recent study involving 75 children with HSPN found that T1/T2 was an independent predictor of renal outcome, whereas the effect of S1 was dependent on the other variables [17].…”
Section: Discussionmentioning
confidence: 98%
“…Pooled analysis of the predictability of MEST and MEST-C scores for HSPN patients was performed using four previous studies [16][17][18][19], although the relationship for C score in adults could not be determined because the C score was defined differently in one study [19]. Two hundred ninety-two children and 235 adults were included in the meta-analysis, and their information is summarized in Table 4.…”
Section: Pooled Analysis With Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation